Pollux, a novel Drosophila adhesion molecule, belongs to a family of proteins expressed in plants, yeast, nematodes, and man. - Zhang, S.D.; Kassis, J.; Olde, B.; Mellerick, D.M.; Odenwald, W.F. (Genes & Development, 1996)
Adhesion molecules have pivotal roles in cellular processes critical to the development and maintenance of multicellular organisms. Here we describe a new member of the adhesive repertoire encoded by the Drosophila pollux (plx) gene. Marked by a novel 74-amino-acid domain, Plx belongs to a highly conserved family with members in plants, yeast, nematodes, and man, including the human oncoprotein TRE17. Essential for viability, plx mutant analysis indicates that larval death is attributable to asphyxiation brought on by fluid-congested tracheal tubes. Ultrastructural examination of mutant tracheae reveals defects in cell-extracellular matrix contacts. During embryogenesis, Plx uniformly covers the apical surface of cellular blastoderm cells. It is later found regionally concentrated along subsets of central nervous system axon pathways and on the apical surface of the trachea's tubular epithelium. Cell attachment assays demonstrate that Plx can serve as a ligand for cell surface integrins. Plx also contains a motor neuron-selective adhesive site, multiple proteoglycan-binding motifs, and a leucine zipper: all suggest possible associations with additional components of the adhesion complex.